Fundamentals of biomechanics - Knudson, Duane (Sparinger, 2021)
This third edition introduces the exciting world of how human movement is created and how it can be enhanced. The book presents a comprehensive review of the major concepts of biomechanics and summarizes them in nine principles of biomechanics. Throughout the text are numerous examples of applying these principles to the work of kinesiology professionals with references to current biomechanics research. Specific case studies illustrate how biomechanics principles can be used in evidence-based practice by professional to modify movement in teaching/coaching and exercise/rehabilitation settings. This text presents a clear, conceptual understanding of biomechanics and is designed to help students through active learning lab activities to link their personal experience to people to improve movement and decrease the risk of injury, as well as advanced students learning biomechanical principles in biomechanical engineering, ergonomics, kinesiology, physics, and sports physiology will find Fundamentals in Biomechanics, 3rd edition invaluable